Methodology to improve profitability in a company textile industry through the improvement of the recruitment and selection process of human resources using Lean Six Sigma and digital transformation - Mas, Daniela Cueva (2023)
Abstract– Micro, small and medium-sized enterprises (MSMEs) represent 90% of the companies incorporated in the world, their importance is such that they generate between 60% and 70% of employment and 50% of GDP; the Peruvian case is not different from this context since MSMEs generate 85% of employment and contribute 84% of GDP. These companies develop their productive and commercial activity in different economic sectors, including textiles and clothing; This sector, which represents 7.2% of the gross domestic product (GDP), concentrates approximately 700,000 workers and has been growing at average rates of 40% in recent years. However, despite the dynamism and importance of this sector, productivity is extremely low; This is due to different factors, one of these being human capital management; this factor is related to the deficient processes of selection, hiring and training of personnel, which makes it difficult for these companies to have at all times workers who have the skills required to perform in the production processes and thus boost the competitiveness of this sector. To overcome these deficiencies, it has been established as the main objective in the following research to implement an agile and efficient model in the selection, hiring and training processes, which allows reducing staff turnover and contributing to the improvement of productivity based on Digital Transformation and the Lean Six Sigma methodology.